1998
DOI: 10.1055/s-2007-1010249
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Coronary Perfusion Changes in Cardiac Dysfunction Associated With Brain Death.

Abstract: Backg round: Previous studies described a hem odynamic insta bility in the pote nt ial orga n don or which has clinical relevance for cardiac t ransplantation. The possible pathophysiological link between altered loadin g conditio ns, coronary perfu sion. and ca rdiac function afte r brain death has not been investiga te d yet. Ther efore this st udy was und ert aken to invest igat e t he ro le of corona ry perfu sion changes durin g brain death in cardiac dysfunction. Methods : Dogs o n card iopulmonary bypas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Contraction band necrosis occurs frequently in individuals who survived for a prolonged period after an intracranial hemorrhage. Recent experimental investigations demonstrated that acute brain death caused by increased intracranial pressure results in a transient increase in myocardial adenosine and lactate, which indicates that oxygen demand exceeds oxygen delivery during the sympathetic storm [36]. In conclusion, in pig brain death models the sympathetic storm produced transient contractile dysfunction, consistent with ischemic injury during brain death [37,38].…”
Section: Morphological Changes In Donor Organs After Brain Deathmentioning
confidence: 99%
“…Contraction band necrosis occurs frequently in individuals who survived for a prolonged period after an intracranial hemorrhage. Recent experimental investigations demonstrated that acute brain death caused by increased intracranial pressure results in a transient increase in myocardial adenosine and lactate, which indicates that oxygen demand exceeds oxygen delivery during the sympathetic storm [36]. In conclusion, in pig brain death models the sympathetic storm produced transient contractile dysfunction, consistent with ischemic injury during brain death [37,38].…”
Section: Morphological Changes In Donor Organs After Brain Deathmentioning
confidence: 99%
“…The mechanisms of myocardial damage are related to excessive activation of cardiac sympathetic nervous system. Its neurotransmitters (catecholamines, NPY) either directly or through inadequate coronary blood flow induce myocardial dysfunction (19,20,22,(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Although the donor heart is a healthy organ, the influences on cardiovascular function of several neuroendocrine disturbances caused by brain death are still to be fully explained. [18][19][20][21][22][23] Because of organ shortage and the need for emergency operation, the graft is sometimes retrieved from a donor situated over 500 km from the place of implantation, so that the ischemic time period may exceed 3 h. A reliable technique of graft preservation would not only improve early and late results of cardiac transplantation, but also allow for an increased number of transplant procedures.…”
Section: Discussionmentioning
confidence: 99%